2021
DOI: 10.1111/jeb.13949
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of seed mass associated with mating systems in multiple plant families

Abstract: In flowering plants, the evolution of self‐fertilization (selfing) from obligate outcrossing is regarded as one of the most prevalent evolutionary transitions. The evolution of selfing is often accompanied by various changes in genomic, physiological and morphological properties. In particular, a set of reproductive traits observed typically in selfing species is called the “selfing syndrome”. A mathematical model based on the kinship theory of genetic imprinting predicted that seed mass should become smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Mazer et al [96] found that the selfing taxon had smaller seeds than outcrossers in each taxon pair, while the local climate was also associated with seed size [96]. Second, a largescale statistical analysis using 642 species from three plant families revealed that selfing species generally have smaller seed mass compared with outcrossing congeners, by controlling for possible confounding factors such as phylogeny and growth forms [97]. These results are consistent with the parental conflict hypothesis, but there are also non-mutually exclusive alternative hypotheses, such as colonization ability, which should be associated with both selfing and small seeds, and the prediction of sex allocation theory, in which the P/O ratio should increase linearly with increasing seed mass among seeding plants [98].…”
Section: Other Notable Traits Associated With the Evolution Of Selfingmentioning
confidence: 99%
“…Mazer et al [96] found that the selfing taxon had smaller seeds than outcrossers in each taxon pair, while the local climate was also associated with seed size [96]. Second, a largescale statistical analysis using 642 species from three plant families revealed that selfing species generally have smaller seed mass compared with outcrossing congeners, by controlling for possible confounding factors such as phylogeny and growth forms [97]. These results are consistent with the parental conflict hypothesis, but there are also non-mutually exclusive alternative hypotheses, such as colonization ability, which should be associated with both selfing and small seeds, and the prediction of sex allocation theory, in which the P/O ratio should increase linearly with increasing seed mass among seeding plants [98].…”
Section: Other Notable Traits Associated With the Evolution Of Selfingmentioning
confidence: 99%
“…Papers which address the interplay of selfing at a multi-family level with other various topics in ecology and evolution have been especially prolific. For example, selfing has been explored in conjunction with geographic range dynamics (Grossenbacher et al 2015(Grossenbacher et al , 2016, invasive status and naturalization (Rananjatovo et al 2016), island biogeography (Grossenbacher 2017), within-population selfing rate variation (Whitehead et al 2018), life history and range size (Prior and Busch 2021), and seed size (Tateyama et al 2021). Additionally, studies focused on estimating rates of transitions to and from selfing using phylogenetic comparative methods (PCMs) have contributed significantly to knowledge about the tempo and mode of selfing evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The change from allogamy (geitonogamy and xenogamy) to autogamous self-fertilisation is usually associated with a selfing syndrome – a characteristic set of changes in floral morphology and function that promote autonomous selfing [ 16 , 29 ]. As has been demonstrated in a number of plant genera, predominantly selfing species have less conspicuous floral display in the form of a smaller number and size of flowers and fewer simultaneously open flowers than their outbreeding relatives [ 5 , 30 , 31 ], smaller and lighter seeds [ 32 35 ], reduced pollen-to-ovule ratio [ 36 ], and lower nectar and scent production [ 37 40 ].…”
Section: Introductionmentioning
confidence: 99%